2024
DOI: 10.1101/2024.06.03.597273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-range neuropeptide relay as a central-peripheral communication mechanism for the context-dependent modulation of interval timing behaviors

Tianmu Zhang,
Zekun Wu,
Yutong Song
et al.

Abstract: Neuropeptides play crucial roles in regulating context-dependent behaviors, but the underlying mechanisms remain elusive. We investigate the role of the neuropeptide SIFa and its receptor SIFaR in regulating two distinct mating duration behaviors in maleDrosophila: Longer-Mating-Duration (LMD) and Shorter-Mating-Duration (SMD). We found that SIFaR expression in specific neurons is required for both LMD and SMD behaviors. Social context and sexual experience lead to synaptic reorganization between SIFa and SIFa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 84 publications
0
0
0
Order By: Relevance
“…Although the specific population of neurons in the EB relies on the foraging gene for the induction of LMD, there may also be a non-neuronal contribution from the foraging gene to elicit LMD behavior. This is supported by our recent findings that corazonin receptor (CrzR), a gene expressed in glial cells, is a crucial component for LMD 48 . Recent studies have indicated that the foraging gene is expressed across various tissues and is not confined to neuronal populations, extending its reach to glial subtypes and peripheral tissues such as the gastric and reproductive systems 49 .…”
Section: Expression Of Foraging In Pdfr-expressing Specific Cell Popu...supporting
confidence: 60%
“…Although the specific population of neurons in the EB relies on the foraging gene for the induction of LMD, there may also be a non-neuronal contribution from the foraging gene to elicit LMD behavior. This is supported by our recent findings that corazonin receptor (CrzR), a gene expressed in glial cells, is a crucial component for LMD 48 . Recent studies have indicated that the foraging gene is expressed across various tissues and is not confined to neuronal populations, extending its reach to glial subtypes and peripheral tissues such as the gastric and reproductive systems 49 .…”
Section: Expression Of Foraging In Pdfr-expressing Specific Cell Popu...supporting
confidence: 60%